Automatic Measurement on Learning Effectiveness towards English Pronunciation Application using Paired sample T-Test - Muhammad Irsad Alfajri; Fazrol Rozi; Meri Azmi; Sariani Sariani; Fithratul Miladiyenti (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2023)
In recent years, it is significant for the higher education students to have the proficiency in English. Most of theseinstitutions set this language proficiency as one of the requirements for their students to graduate. They have been designingandestablishing various ways on how to increase the student’s proficiency, particularly in pronunciation skill. However, theresultsobtained are yet satisfactory. As a matter of fact, in measuring the English pronunciation skill, the guidance fromthe expertsornative speakers are still needed. Thus, the development of the artificial intelligence nowadays can have great contributiontoreplacethe existence of these experts by integrating it into the pronunciation learning. The aim of this research was to establishatrainingsystem in pronunciation, to provoke the students’ self-directed learning. Besides that, this system was also developedinordertoautomatically measure the learning effectiveness by employing the paired sample t-test. The results show that the systemthathasbeen established can measure the percentage of the student’s pronunciation accuracy in each utterance they make, and whetherthereis a essential improvement in students pronunciation ability.